2021
DOI: 10.1080/13683500.2021.1884666
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the impacts of tourism-based social media, risk perception and fear on tourist’s attitude and revisiting behaviour in the wake of COVID-19 pandemic

Abstract: To cite this article: Raouf Ahmad Rather (2021): Monitoring the impacts of tourism-based social media, risk perception and fear on tourist's attitude and revisiting behaviour in the wake of COVID-19 pandemic, Current Issues in Tourism,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
129
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 218 publications
(149 citation statements)
references
References 33 publications
11
129
1
8
Order By: Relevance
“…While social media has been extensively researched in the tourism and travel literature (e.g. Milano et al, 2011;Xiang & Gretzel, 2010), issues related to misinformation appear relatively limited in the current pandemic context (Rather, 2021). Williams et al (2020) hypothesize that with the release of the COVID-19 vaccines, attitudes towards the vaccine take-up could have significant impacts on travel intentions.…”
Section: Protection Motivation Theory and Covid-19 Vaccinationmentioning
confidence: 99%
“…While social media has been extensively researched in the tourism and travel literature (e.g. Milano et al, 2011;Xiang & Gretzel, 2010), issues related to misinformation appear relatively limited in the current pandemic context (Rather, 2021). Williams et al (2020) hypothesize that with the release of the COVID-19 vaccines, attitudes towards the vaccine take-up could have significant impacts on travel intentions.…”
Section: Protection Motivation Theory and Covid-19 Vaccinationmentioning
confidence: 99%
“…Most of the early literature may be limited to the exploration of a wide range of issues related to the quantitative or qualitative nature of second-hand data analysis related to tourism issues [23][24][25][26][27], tourism management issues and related strategic issues under the pandemic [28][29][30][31][32][33], and the satisfaction issues of accommodation and restaurants under the pandemic [34][35][36][37]. Some of the researchers study the economic issues that affect the tourism industry in the COVID-19 pandemic [38][39][40][41][42][43][44], discuss the psychological issues of travel stakeholders in the pandemic [45][46][47][48][49][50], or perform research on Tourism and Virtual Reality (VR) [51][52][53]. Past research has focused on six functions.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization is investigating the potential to create travel "corridors" or "bubbles" as the first step in expanding countries tourism opportunities. They have found that countries with a comparable number of COVID-19 cases and good case management processes are planning to use these approaches to facilitate international travel, for example, Singapore and Thailand [37].…”
Section: -4-lifting Travel Restrictionsmentioning
confidence: 99%